2010
DOI: 10.1089/jmf.2009.1142
|View full text |Cite
|
Sign up to set email alerts
|

A Lipid-Soluble Red Ginseng Extract Inhibits the Growth of Human Lung Tumor Xenografts in Nude Mice

Abstract: Lipid-soluble ginseng extract was prepared by n-hexane extraction of red ginseng. BALB/c-nu mice were inoculated with human lung cancer (NCI-H460) cells to establish a human tumor xenograft model in nude mice, and the lipid-soluble ginseng extract was orally administered. The tumor inhibitory rates of the lipid-soluble ginseng extract at doses of 0.1, 0.3, and 1.0 g/kg/day were 18.9% (P < .05), 60.0% (P < .001), and 67.5% (P < .001), respectively. The oral administration of the lipid-soluble extract of red gin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 26 publications
3
48
0
Order By: Relevance
“…Polyacetylenes containing panaxynol, panaxydol, and panaxytriol have been regarded to be responsible for these anticancer effects in LSGE [11,12]. In our previous report, the content of polyacetylenes in LSGE was considered to be 2.38~6.88% and panaxynol was identified as a dominant compound [13]. Also, LSGE possessed an anticancer activity against NCI-H460 human lung tumors in murine xenograft models in a dose-dependent manner without any apparent sign of toxicity [13,14].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Polyacetylenes containing panaxynol, panaxydol, and panaxytriol have been regarded to be responsible for these anticancer effects in LSGE [11,12]. In our previous report, the content of polyacetylenes in LSGE was considered to be 2.38~6.88% and panaxynol was identified as a dominant compound [13]. Also, LSGE possessed an anticancer activity against NCI-H460 human lung tumors in murine xenograft models in a dose-dependent manner without any apparent sign of toxicity [13,14].…”
Section: Introductionmentioning
confidence: 97%
“…In our previous report, the content of polyacetylenes in LSGE was considered to be 2.38~6.88% and panaxynol was identified as a dominant compound [13]. Also, LSGE possessed an anticancer activity against NCI-H460 human lung tumors in murine xenograft models in a dose-dependent manner without any apparent sign of toxicity [13,14]. Although the anticancer activity of LSGE was reported to be derived from G1 cell cycle arrest [15], little is known regarding the molecular mechanism of LSGE-induced anticancer effects.…”
Section: Introductionmentioning
confidence: 99%
“…According to our findings, 6-year-old ginseng can easily be distinguished from ginseng over 8 years old by detecting the amount of the characteristic compositions falcarinol (8) and 10,12-octadecdiynoic acid (12) and the nonspecific composition sitosterol by the GC-MS method.…”
Section: Discussionmentioning
confidence: 52%
“…In addition to linoleic, palmitic, oleic and linolenic fatty acids and principal sesquiterpene components [4,5], polyacetylenes including panaxytriol, falcarinol and ginsenoyne A-K are present in ginseng as typical diyne lipid components [1,[6][7][8]. Recent studies reported that the nonpolar components of ginseng have antioxidant, antimicrobial, antitumor and anti-obesity activities [9][10][11][12]. A compound having pharmacological activity (such as falcarinol) could be found among them [13].…”
Section: Introductionmentioning
confidence: 99%
“…KBH-A42 was dissolved in dimethyl sulfoxide (DMSO) and freshly diluted in culture media for all in vitro experiments. Female BALB/c-nu mice were purchased from SLC (Hamahatsu, Japan) and maintained as previously described (14). All animals were permitted to acclimate to the local environment for at least 1 week prior to use.…”
Section: Introductionmentioning
confidence: 99%